ANALISIS TEKNOLOGI INFORMASI MOBILE BANKING DAN PERSEPSI RISIKO TRANSAKSI TERHADAP KEPUASAN NASABAH (Studi Kasus Bank Mandiri Syariah Cabang Jemur Handayani Surabaya) - Soelistya, Djoko; Agustina, Heni Agustina (JURNAL AKUNTANSI DAN MANAJEMEN, 2018)
In this era of technology now a very important role in the banking business the role of technology is absolute, where in the banking system of information technology is needed to support the progress of the banking system. The purpose of this research is to know about the effect of Information Technology of banking car and Risk Transaction Perception on Banking Customer Satisfaction, because many people only think about the interest in the use of banking facilities but not many banks know the feeling of satisfaction that exist within the customer over the facility. This research is quantitative research with explanative research type by doing observation because it explains the relation between variables through hypothesis testing without giving treatment with sample taken from a population using questionnaire as primary data gathering tool, and generally is unit of individual analysis. The population taken as many as 155 respondents, taken from the respondent employees UNUSA Yayasan RSI Surabaya. The results of this study found that a significant value variable Perception of Technology (X1) 0,000